Managing Disputes in the Construction Sector: The Perspective of Project Managers - Emine YAVUZ; Savaş BAYRAM; Mahmut SARI (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
The global construction industry is expected to increase by 42% between 2020 and 2030; its contribution to national economies is rising. However, this growth increases the disputes that arise during project management processes. Disputes place an additional burden on the judicial system and cause serious economic losses. Therefore, it is of great importance to develop more effective processes. This research examines the root causes of disputes and proposes solutions. Within the scope of the study, the ability of project managers, directly involved in all stages of construction projects, to evaluate these disputes from a broad perspective is examined. In this context, a survey was administered to project managers who have worked on construction projects in Türkiye and have been involved in disputes, and 123 valid data points were collected. The results were analyzed with the Mann-Whitney U and Kruskal-Wallis tests. The study includes the preliminary findings of a master's thesis.